Determination of an Empirical Model between California Bearing Ratio and Aggregate Crushing Value of Base Course Materials of Selected Sources in Madhesh Province - Malepati, Ram Kumar; Gautam, Gopal (Journal of Advanced College of Engineering and Management, 2025)
The research study focuses on evaluating the physical properties of base course aggregates from various river sources in Madhesh Province and their suitability for road construction, based on the "SSRBW 2016 (2nd Amendment 2022)" by the Department of Roads (DoR). Sixty-six aggregate samples from twenty-two rivers were tested in accordance with IS codes and DoR testing manuals. The study aimed to assess strength and durability, particularly analyzing the relationship between Aggregate Crushing Value (ACV), and California Bearing Ratio (CBR) Value. Results showed that 21 out of 22 sources met the required specifications. Seventy-five percent of suitable samples were used for regression analysis to develop an empirical relationship between CBR and ACV , while the remaining percent were used for model validation. A strong correlation (R² = 0.8444) was found, indicating that ACV can be a reliable substitute for CBR testing, simplifying and expediting aggregate evaluation for pavement design.